دور العوامل الجغرافية في تقسيم اقليم جنوب كوردستان عام 1916 - البوتاني, طلعت محمد طاهر (Sulaimani Journal for Humanities, 2018)
ABSTRACT Kurdistan is considered as an integrated geographical unit but had been divided due to migration and wars that have faced the people of the area since the dawn of history until now. Due to its active political geography, Kurdistan has become the theater for global conflicts and wars that resulted in instability and retardation; this has negatively influenced the development of Kurdish nation. As a result, Kurdistan had been divided between Ottoman and Safavid empires starting from the battle of Chaldiran in 1514. Therefore, studying geographical and spatial factors and their impact on the division of Kurdistan in general and southern Kurdistan in particular in the Sykes-Picot agreement between Britain, France, and Russia that has annexed southern Kurdistan to Iraq is critical. The borders drown by the terms of Sykes-Picot are imposed on the Kurdish people, and the interests of Kurdish population are not considered. Furthermore, the natural and human Geographical characteristics of the area are not taken into account. The southern parts of Kurdistan have distinct natural and human resources that are of particular economic interest. In case of the unity of the Kurdish territories, these natural resources can significantly qualify to become an influential geopolitical power in historical, geographical, economical, cultural, and political aspects in the Middle East